Political developments in Nigeria 1960-1976 (Journal of the College of Basic Education, 2022)
Our research focuses on the study of political developments in Nigeria since 1960, which is the year of coups, the first coup in January 1960 and the second coup in July 1960. The research also studied the Nigerian civil war 1967-1970 and the repercussions of this war on society and political events in Nigeria. The country's president with many military leaders and the repercussions of that coup on Nigeria